Analysis of Methanolic Extracts and Crude Polysaccharides from the Leaves of Chuanminshen violaceum and Their Antioxidant Activities - Lin, Shang (Antioxidants (Basel), 2019)
The root of Chuanminshen violaceum is used as an important edible and medicinal plant in China. However, its leaves are generally considered byproducts, and therefore do not have a use. Thus, the phenolic compounds in the methanolic extracts (CVLMs) and the chemical characteristics of crude polysaccharides (CVLPs) from the leaves of C. violaceum and their in vitro antioxidant activities were explored. The results showed that chlorogenic acid and rutin were the major individual phenolic compounds in the leaves, which ranged from 1.22 ± 0.03 to 2.87 ± 0.04 mg/g DW, and from 2.25 ± 0.04 to 4.03 ± 0.05 mg/g DW, respectively. Meanwhile, the extraction yields of CVLPs from the leaves ranged from 4.73% to 5.41%. The CVLPs consisted of mannose, rhamnose, galacturonic acid, glucose, galactose, and arabinose, suggesting the existence of pectic polysaccharides. Furthermore, both CVLMs and CVLPs exhibited strong antioxidant activities. Chlorogenic acid and rutin were major contributors to the antioxidant activities of CVLMs, and the antioxidant activities of CVLPs were closely correlated to their α-1,4-D-galactosiduronic linkages. The results are beneficial for understanding the chemical properties and in vitro antioxidant activities of CVLMs and CVLPs. The leaves of C. violaceum have potential to be developed as natural antioxidants.